Individual and Collective Responses to Crisis: An Analytical Framework for the Study of Social Resilience - Medrano, Juan Díez (PARTECIPAZIONE E CONFLITTO, 2014)
This article proposes a sociological approach for the study of social resilience that emphasizes interpretation and the role of networks. After discussing past contributions to the study of social resilience and proposing an alternative analytical framework that builds on Max Weber’s approach to social action, the article illustrates the proposed strategy through a discussion of the acquisition of transnational skills as a strategy of social resilience. Available empirical evidence shows indeed that fluency in foreign languages works both a resilience strategy and a vehicle toward the emergence of an European demos